DOP25 Contraceptive method use according to Inflammatory Bowel Disease status among young women in the United States. (30th January 2023) - Brenner, E; Zhang, X; Long, M; Dubinsky, M; Kappelman, M
Abstract: Background: Inflammatory bowel disease (IBD) and estrogen-based contraceptives both increase thromboembolism risk, leading gastroenterologists to recommend long-acting reversible contraceptives (LARCs) over estrogen-based methods for women with IBD. No study has evaluated whether young women with IBD follow this guidance, especially as many patients lack awareness of estrogen-related risks, and young women generally prefer estrogen-based methods. We evaluated contraceptive use patterns for young women with versus without IBD, including odds of estrogen-based contraceptive use. Methods: Using the IQVIA Pharmetrics Plus Database, a United States (US) health insurance claims database, we identified US women ages 15-25 with ≥1 prescription contraceptive and ≥6 months continuous enrollment from enrollment start to first contraceptive code (intake period). We excluded patients with ≥1 hysterectomy/sterilization claim during intake. The independent variable was IBD diagnosis, defined as ≥3 codes for Crohn's disease (CD) or ulcerative colitis (UC), 2 CD and/or UC codes and 1 IBD medication code, or 1 CD or UC code and 2 IBD medication codes during intake. The dependent variable was estrogen-based contraceptive use (estrogen-based contraceptive pill, patch, and ring) versus non-estrogen-based (progestin-only pill, injectable, implant, and intrauterine device [IUD]), based on the first contraceptive claim. We generated descriptive statistics for contraceptive sub-type and covariates stratified by IBD status and performed bivariate comparisons. Using multivariable logistic regression, we determined adjusted odds ratios (aOR) with 95% confidence intervals (CI) for estrogen-based contraceptive use, adjusting for age, region, year, and insurance. Results: We identified 802, 932 young women on contraceptives, of whom 1, 083 had IBD. Demographics were similar across IBD status except more women with IBD had commercial insurance (Table). Use of the estrogen-based pill, patch, and ring was similar or marginally lower for women with IBD versus without IBD (67.6% vs 68.8%, 2.7 vs 3.1%, and 1.5 vs 1.4%). Women with IBD had a slightly higher proportion of implant use and similar IUD use versus those without IBD (16.1% vs 14.2%; 1.8% vs 1.7%, ) (Table, Figure). After adjustment, young women with IBD were 0.82 times as likely to use estrogen-based contraceptives compared to those without IBD (aOR 0.82; 95% CI 0.71-0.94). Conclusion: Young women with IBD on contraceptives are only slightly less likely to use estrogen-based methods as those without IBD, despite the recommendation for LARC over estrogen-based contraceptives in IBD. This finding suggests a need for reproductive health education efforts and contraceptive safety studies specific to young women with IBD.